PENERAPAN MODEL PEMBELAJARAN TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 014 BERINGIN MAKMUR KECAMATAN KERUMUTAN KABUPATEN PELALAWAN - Husni Armi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low result of fifth grade students learn math SDN 014Beringin Makmur Kecamatan Kerumutan. The low yield of this study are (a) the learningmethod used by the teacher is conventional; (b) learning is teacher centers; and (c) theteacher is not able to manage the classroom so that learning is less than optimal. The purposeof this research is to improve students' mathematics learning outcomes by applying the modelof guided learning. This research is a class act, who performed two cycles. The data used inthis research is data result of learning mathematics. Based on the results of the study revealedthat the results of learning mathematics has increased. This is evidenced in the preliminarydata the number of students who completed totaling 12 students. In the first cycle the numberof students who pass increases with the number of 22 students and the second cycle increaseswith the number of students who completed by 24 students.